English Learning in Islamic University in The Context of ESP: English For Specific Purpose - Nining Wulandari (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2020)
Briefly, this paper discusses of learning English for the one of the formal education students who provide foreign language instruction is an Islamic University. In Islamic University, foreign languages ​​are one of important course that students must take. The foreign language is English. The field of teaching English with a specific purpose or more known as English for Specific Purpose (ESP) is a teaching field English which is relatively new by adjusting the scientific majors in Universities. By teaching English in Islamic universities, it is expected Students are able to study Islamic science in foreign languages, especially English and are able to follow the development of world globalization that demands someone can master foreign languages.